2021
DOI: 10.7200/esicm.53.277
|View full text |Cite
|
Sign up to set email alerts
|

El reto de la alfabetizacion financiera digital en el ámbito de la fintech (industria 4.0)

Abstract: Objetivo: el artículo tiene como objetivo principal el analizar el nivel de cultura financiera digital o alfabetización financiera digital de los estudiantes en centros universitarios españoles en el marco de la Industria 4.0. Se incluye una nueva medida original para medir el grado conocimientos financieros digitales, en función de un cuestionario elaborado ad-hoc. Metodología: se diseñó una encuesta partiendo de las recomendaciones dadas en la literatura más actual. Se aplicó el cuestionario durante la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It remains to be determined whether those who perceive more excellent skills are also users who leverage the opportunities that financial institutions offer them. Previous studies (Gallego-Losada et al, 2021;Latheef and Sunitha, 2016) have shown that the literacy level is even lower when evaluating the implementation of the competency, which has implications for future research. Higher digital financial literacy could lead to better results in managing personal finances.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It remains to be determined whether those who perceive more excellent skills are also users who leverage the opportunities that financial institutions offer them. Previous studies (Gallego-Losada et al, 2021;Latheef and Sunitha, 2016) have shown that the literacy level is even lower when evaluating the implementation of the competency, which has implications for future research. Higher digital financial literacy could lead to better results in managing personal finances.…”
Section: Discussionmentioning
confidence: 95%
“…In digital financial literacy, young adults thought they had a higher level of financial literacy than they did (Latheef and Sunitha, 2016). Specifically, the Gallego-Losada et al (2021) study evidences the disparity in measuring digital financial competency in young people. There is an intermediate level in the self-perception of digital financial knowledge, skills, and attitudes and a lower level when they must tangibly demonstrate digital financial competency.…”
Section: Theoretical Backgroundmentioning
confidence: 98%